Sistem Informasi Booking Lapangan Badminton dengan Fitur Find Match Menggunakan Framework Laravel pada Gor Pratama - Muhammad Edo Wardaya, Edo; Ilham Aristanto; Wendy Asswan Cahyadi (Sekolah Tinggi Ilmu Komputer El Rahma, 2025)
This study aims to develop a Badminton Court Reservation Information System with the Find Match feature using the Laravel framework at Gor Pratama. The problem encountered is the lack of complete information for prospective customers when making reservations, especially regarding court schedules. This results in customers always having to inquire about court availability on their desired date and time before making a reservation. The high number of similar questions simultaneously can make it difficult for field managers to determine schedules, especially because the scheduling process is still manual and requires repeated writing or changes to existing schedules. Furthermore, there is also the possibility that customers do not have friends or opponents to play with before making a reservation. In this study, the Big Bang Model software development method was used using UML as the system development model. Software testing was conducted through black-box testing. Research data was collected through observation, interviews, and literature review. The results show that the Badminton Court Reservation Information System with the Find Match feature successfully facilitates the process of booking courts, creating schedules, and providing options for customers who do not have friends to play with.